Programa de Aquisição de Alimentos (PAA) da agricultura familiar no município de São Carlos: impactos socioeconômicos nos agricultores familiares beneficiários - Rossi, Fabiana Ribeiro (2012)
The Food Acquisition Program from Family Farm (PAA) was created in 2003, within a group of policies with structural significance of the Zero Hunger Program, in order to promote actions in the scope of agricultural policies and food security. Its operation is made through modalities that purchase products from family farmers, without bidding. The PAA, since its institutionalization, has been the focus of several analyzes, as their impacts on the family farmers beneficiaries. This dissertation aimed to evaluate the impacts on family farmers beneficiaries of the Direct Purchase Local with Simultaneous Donation (CDLDS), executed since 2006, in the city of São Carlos, by the Municipal Agriculture and Food Supply (SMAA). The data collection was done by applying a structured questionnaire to a representative sample of 30 beneficiaries of the program in São Carlos and adjacent municipalities. The data were analyzed using descriptive statistics and hypothesis testing, which allowed the identification of positive impacts of the program in aspects related to their life conditions, land use, crop production, commercialization of products, agricultural income, association, family assets, investment properties, access to rural extension and information, agricultural practices, quality management, among others. No significant impacts were identified in aspects related to property management techniques and production, access to rural credit, participation of women, among others. The PAA can be considered an important program for family farmers beneficiaries because it is an alternative market channel to sale the production, collaborating, through its set of actions, with a more sustainable inclusion of its beneficiaries in other markets.